2023
DOI: 10.1109/access.2023.3234421
|View full text |Cite
|
Sign up to set email alerts
|

Video Based Mobility Monitoring of Elderly People Using Deep Learning Models

Abstract: In recent years, the number of older people living alone has increased rapidly. Innovative vision systems to remotely assess people's mobility can help healthy, active, and happy aging. In the related literature, the mobility assessment of older people is not yet widespread in clinical practice. In addition, the poor availability of data typically forces the analyses to binary classification, e.g. normal/anomalous behavior, instead of processing exhaustive medical protocols. In this paper, real videos of elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Ref. [4] describes a study involving the analysis of videos of elderly people performing three mobility tests and how the videos could be automatically categorized using deep neural networks in order to emulate how they are evaluated by expert physiotherapists. It was found that the best results were achieved by a deep Conv-BiLSTM classifier.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [4] describes a study involving the analysis of videos of elderly people performing three mobility tests and how the videos could be automatically categorized using deep neural networks in order to emulate how they are evaluated by expert physiotherapists. It was found that the best results were achieved by a deep Conv-BiLSTM classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Each LFBL (represented by the next five red blocks) consists of a 2D-CNN, batch normalization, activation, max pooling, and a dropout (20% random drop) layer. The CNN layers within each LFBL are of sizes 64, 64, 128, and 128, and the corresponding max pooling sizes are (2,2), (4,4), (4,4), and (4,4). After the last LFBL, a fully connected layer is used to convert the output of the LFBL into a one-dimensional vector, which is then passed to the LSTM layer (green).…”
Section: Emotion Detection Systemmentioning
confidence: 99%
“…A typical approach to compare our research findings to related work is by evaluating the performance of the proposed machine learning models based on the commonly used evaluation metrics such as accuracy, precision, recall, and F1-score on various datasets. This approach is widely adopted in almost every research in the area of machine learning models design [45], [46], [47], [48]. In a similar manner, we compared the proposed approach to related work by applying them to the same dataset and using the same metric to evaluate their performance.…”
Section: ) Comparison To Related Workmentioning
confidence: 99%
“…Human activity recognition (HAR) systems monitor activity patterns and intervene when a change in behavior or a critical event has occurred [6][7][8][9][10]. These systems are based on complex architectures that collect data with sensor devices, performing computations and extracting knowledge in order to obtain relevant activity information [11][12][13].…”
Section: Introductionmentioning
confidence: 99%